Réponses

2013-11-19T20:33:24+01:00
28.   
4x+4=4(x+1)
8x-8=8(x-1)
4+2x=2(2+x)
2x-8=2(x-4)
9x²-5x=x(9x-5)
6x+9=3(2x+3)

29.
x(x+5)+x(3x-2)=x(x+5+3x-2)=x(4x-3)
(5+x)(2x+1)+6(2x+1)=(2x+1)(5+x+6)=(2x+1)(x+11)
-4x(2x+3)+(2x+3)(9-2x)=(2x+3)(-4x+9-2x)=(2x+3)(-6x+9)=-3(2x+3)(2x-3)
-8x(5x-1)-8x(12-x)=-8x(5x-1+12+x)=-8x(6x+11)

32.
(x+3)(y+9)+x+3=(x+3)(y+9)+(x+3)=(x+3)(y+9+1)=(x+3)(y+10)
(a-5)(7+b)-(7+b)=(7+b)(a-5-1)=(7+b)(a-6)
3x+1+(3x-1)(3x+1)=(3x+1)+(3x-1)(3x+1)=(3x+1)(1+3x-1)=3x(3x+1)
x+5+(x+5)(6x+3)=(x+5)+(x+5)(6x+3)=(x+5)(1+6x+3)=(x+5)(6x+4)=2(x+5)(3x+2)

35.
(4x+5)²-(3x-6)(4x+5)=(4x+5)(4x+5)-(3x-6)(4x+5)=(4x+5)(4x+5-3x+6)=(4x+5)(x+11)
(5x-2)²-(5x-2)(x+3)=(5x-2)(5x-2)-(5x-2)(x+3)=(5x-2)(5x-2-x-3)=(5x-2)(4x-5)
(4x-9)(x+7)-(4x-9)²=(4x-9)(x+7)-(4x-9)(4x-9)=(4x-9)(x+7-4x+9)=(4x-9)(-3x+16)
(x+3)(x-5)-(x-5)²=(x+3)(x-5)-(x-5)(x-5)=(x-5)(x+3-x+5)=8(x-5)